Pengaruh Piutang Tak Tertagih, Perputaran Dan Umur Piutang Pasien Jaminan Umum Terhadap Profitabilitas Pada Rsbp Batam - Tya Nursyafira Istighfarin; Hermaya Ompusunggu (SEIKO : Journal of Management & Business, 2023)
The objective of this study is to identify and evaluate how bad debts, receivables turnover, and age of receivables affect the profitability of BP Batam Hospital's financial statements. The financial accounts of the BP Batam hospital from 2017 to 2021, totaling 60 data, are the population of this study. Purposive sampling was used in this study's sampling process to ensure that a total of 41 data were included in the sample. The financial statements used in this study were collected from http://fbms.bpbatam.go.id as secondary data. The SPSS device is used for data testing. In this study, descriptive analysis, traditional assumption testing, multiple linear analysis, and hypothesis testing were employed in the data analysis. According to the study's findings, bad debts, receivables turnover, and account receivable age have no combined impact on profitability. Furthermore, the profitability of BP Batam Hospital for the years 2017–2021 is not significantly impacted by bad debts, receivables turnover, or age of receivable. Keywords : Uncollectible Accounts, Accounts Receivable Turnover, Receivable Age, Profitability.